Exploring Ethiopian Secondary School Science Teachers' Conceptions about the Nature of Scientific Knowledge (NOSK) - Tadele Demelash Teshale; Reda Darge Negasi; Dawit Asrat Getahun (MDPI AG, 2024)
This study examined secondary school science teachers' conceptions of the nature of scientific knowledge (NOSK). The participants were convenient samples consisting of 48 (M = 38, F = 10) teachers from three secondary schools. An open-ended questionnaire was administered to collect data. Qualitative analysis involved comparing teachers' responses to experts' views on NOSK. Frequency counts and percentages were also used to describe the NOSK conceptions of participants. Based on the findings, the teachers held informed conceptions on two NOSK tenets and naïve conceptions on four of them. The participants generally held a naïve conception of NOSK, as evidenced by the fact that their conception aligned with informed conception only on two of the seven assessed NOSK aspects. Future research should use large samples, employing a quantitative approach to reveal secondary school teachers' NOSK conceptions.